Wings of fire an autobiography - Abdul Kalam, Avul Pakir Jainulabdeen 1931-; Tiwari, Arun. (Hyderabad, A.P., India Universities Press, 1999)
Autobiography of an Indian scientist.
Keywords: Abdul Kalam, Avul Pakir Jainulabdeen -- 1931-.; Scientists -- India -- Biography